Online education improves pediatric residents' understanding of atopic dermatitis. Issue 1 (29th November 2017) - Craddock, Megan F.; Blondin, Heather M.; Youssef, Molly J.; Tollefson, Megha M.; Hill, Lauren F.; Hanson, Janice L.; Bruckner, Anna L.
Abstract: Background/Objectives: Pediatricians manage skin conditions such as atopic dermatitis (AD) but report that their dermatologic training is inadequate. Online modules may enhance medical education when sufficient didactic or clinical teaching experiences are lacking. We assessed whether an online module about AD improved pediatric residents' knowledge and changed their clinical management of AD. Methods: Target and control cohorts of pediatric residents from two institutions were recruited. Target subjects took a 30‐question test about AD early in their residency, reviewed the online module, and repeated the test 6 months and 1 year later. The control subjects, who had 1 year of clinical experience but had not reviewed the online module, also took the test. The mean percentage of correct answers was calculated and compared using two‐sided, two‐sample independent t tests and repeated‐measures analysis of variance. For a subset of participants, clinical documentation from AD encounters was reviewed and 13 practice behaviors were compared using the Fisher exact test. Results: Twenty‐five subjects in the target cohort and 29 subjects in the control cohort completed the study. The target cohort improved from 18.0 ± 3.2 to 23.4 ± 3.4 correctly answered questions over 1 year ( P < .001). This final value was greater than that of the control cohort (20.7 ± 4.5; P = .01). Meaningful differences in practice behaviors were not seen. Conclusion: Pediatric residents who reviewed an online module about AD demonstrated statistically significant improvement in disease‐specific knowledge over time and had statistically significantly higher scores than controls. Online dermatology education may effectively supplement traditional clinical teaching.